Overexpressing CCT6A Contributes To Cancer Cell Growth By Affecting The G1-To-S Phase Transition And Predicts A Negative Prognosis In Hepatocellular Carcinoma - Zeng G (OncoTargets and Therapy, 2019)
Guofen Zeng,1,* Jialiang Wang,2,* Yanlin Huang,1,* Yifan Lian,2 Dongmei Chen,2 Huan Wei,2 Chaoshuang Lin,1 Yuehua Huang1,2 1Department of Infectious Diseases, The Third Affiliated Hospital of Sun Yat-sen University, Guangzhou 510630, Guangdong, People’s Republic of China; 2Guangdong Provincial Key Laboratory of Liver Disease Research, The Third Affiliated Hospital of Sun Yat-sen University, Guangzhou 510630, Guangdong, People’s Republic of China*These authors contributed equally to this workCorrespondence: Yuehua HuangDepartment of Infectious Diseases & Guangdong Provincial Key Laboratory of Liver Disease Research, The Third Affiliated Hospital of Sun Yat-sen University, Guangzhou 510630, Guangdong, People’s Republic of ChinaTel +8620-85252702Fax +8620-85253305Email huangyh53@mail.sysu.edu.cnChaoshuang LinDepartment of Infectious Diseases, The Third Affiliated Hospital of Sun Yat-sen University, Guangzhou, Guangdong 510630, People’s Republic of ChinaEmail lchaosh@mail.sysu.edu.cnPurpose: To determine the oncogenic role of the sixth subunit of chaperonin-containing tailless complex polypeptide 1 (CCT6A) in hepatocellular carcinoma (HCC) and address the correlation of CCT6A with clinicopathological characteristics and survival. Additionally, this study aimed to explore the effect of CCT6A on HCC cells and the underlying mechanisms.Methods: We searched for levels of CCT6A expression in the Oncomine database and GEPIA database, which was then validated by analyzing cancer and adjacent non-cancerous tissues of HCC patients using quantitative PCR, Western blot, and immunohistochemistry assays. The relationship between CCT6A expression and survival was analyzed from the GEPIA database and confirmed by immunohistochemistry assays of 133 HCC tissue sections. In addition, the effect of depleting CCT6A on cell proliferation was assessed by CCK-8 and colony formation assays. Cell cycle analysis, immunofluorescence assays, GSEA analysis, and cyclin D expression analyzed by Western blot were used to explore the possible underlying mechanism how dysregulated CCT6A affect the proliferation of HCC.Results: Both mRNA and protein levels of CCT6A were increased in HCC tissues. Higher CCT6A expression was significantly associated with reduced overall survival (P = 0.023). CCT6A depletion inhibited cell proliferation and downregulated cyclin D, hindering the G1-to-S phase arrest.Conclusion: CCT6A may contribute to HCC cell proliferation by accelerating the G1-to-S transition, as it maintains the expression of cyclin D. CCT6A could be considered an oncogene of HCC and could be used as a prognostic biomarker for HCC.Keywords: HCC, survival, CCT6A, cell proliferation, cyclin D